Acute Bacterial Meningitis in Infants and Children - E. Prajogo; Harsono Salimo; Netty R.H.T.; S. Untario (Indonesian Pediatric Society, 1983)
A study of acute bacterial meningitis in infants and children had been reported. Of particular interest in this study was the fact that the results of the CSF cultures revealed the most frequent causative agent to be Diplococcus pneumoniae (35%), with Staphylococcus aureus ranking second (25%). Other causative agents were E. coli (10%), Salmonella paratyphi B (10%), Streptococus pyogenes (5%). Hemophilus influenzae was not found in this study. The mortality rate was 40%.